Roots and fruits of decoherence - Zeh, Heinz-Dieter (Arxiv, 2006)
The concept of decoherence is defined, and discussed in a historical context. This is illustrated by some of its essential consequences which may be relevant for the interpretation of quantum theory. Various aspects of the formalism are also reviewed for this purpose. Contents: 1. Definition of concepts. 2. Roots in nuclear physics. 3. The quantum-to-classical transition. 4. Quantum mechanics without observables. 5. Rules versus tools. 6. Nonlocality. 7. Information loss (paradox?). 8. Dynamics of entanglement. 9. Irreversibility. 10. Concluding remarks.